Lex mercatoria and private international arbitration - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The “New Lex Mercatoria” is not a “legal system” or a defined set of rules, but a “method”. In this sense, the New Lex Mercatoria consists of giving authorization to the courts and/or arbitrators to assess different legal materials regulating international trade; following that, they will extract the “most appropriate rules” to solve the litigation. It is, therefore, a method to achieve adequate decisions in international trade (Method of Decision-Making). Thus, the arbitrator is prevented from applying a single national Law, which is exactly what the parties intended to avoid at all costs and the reason why they chose the New Lex Mercatoria. In other words, it can be affirmed that the methodological approach to the New Lex Mercatoria is the most operative, useful and complete, as well as the one that enables us to develop a metacriticism of the New Lex Mercatoria as a source of Law in international trade.